Effect of sequence depth and length in long-read assembly of the maize inbred NC358 - Shujun Ou (Nature Portfolio, 2020)
Sequence depth and read length determine the quality of genome assembly. Here, the authors leverage a set of PacBio reads to develop guidelines for sequencing and assembly of complex plant genomes in order to allocate finite resources using maize as an example.